2021
DOI: 10.1016/j.annonc.2021.08.840
|View full text |Cite
|
Sign up to set email alerts
|

1511P The demographics of cancer care in a developing country: ten years’ experience from an academic university hospital in India

Abstract: Background: Despite the efforts of scientific organisations, patients' views of immunotherapy are unclear. CareAcross, a multilingual digital platform which provides personalised, evidence-based support to cancer patients, investigated their views on immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, the circumstances of the patients presenting to cancer facilities can also contribute to the observed disparities. For example, a recent study in India found that oncology patients presented at a younger median age, had lower levels of education, were more likely to be financially distressed, and had to travel greater distances to seek specialized treatment [6] . Cost of care is one of the main barriers to patient treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the circumstances of the patients presenting to cancer facilities can also contribute to the observed disparities. For example, a recent study in India found that oncology patients presented at a younger median age, had lower levels of education, were more likely to be financially distressed, and had to travel greater distances to seek specialized treatment [6] . Cost of care is one of the main barriers to patient treatment.…”
mentioning
confidence: 99%
“…A systematic review and meta-analysis by Donkor et al [3] (2022) found that patients in LMICs experience high levels of financial toxicity. Such financial and logistical considerations are often not factored into guidelines, particularly those developed in countries with a high human development index [6] .…”
mentioning
confidence: 99%